Malpractice in pathology: Review [Patolojide tibbi uygulama hatalari] - (:unkn) unknown (Turkiye Klinikleri, 2008)
Medical malpractice may occur during diagnosis, treatment and follow-up. Malpractice cases in pathology usually result from mistakes in diagnosis. The reported clinically significant diagnostic error rate in surgical pathology varies from 0.26% to 1.2%. Nevertheless, the current expectation is no error at all. Pathologists play an important role in diagnosing the patient accurately. Thus, pathologists have to maintain high standard both in their scientific capacity and in technical infrastructure. Identifying the most frequent errors in pathology will contribute to reduce their occurrence. Troxel classified the 6 fields of highest risk in pathology as follows: breast biopsy, cases of melanoma and lymphoma, fine needle aspiration (FNA), frozen section and prostate biopsy. Strategies should be developed and quality control systems should be implemented in order to decrease these errors. Copyright © 2008 by Türkiye Klinikleri.
Keywords: Malpractice; Pathology, surgical; Quality control